Economic Reform and the Demand for Money in China. (IMF Working Papers; Working Paper ;, 1990)
Error correction models of the demand for a range of monetary aggregates in China are estimated with quarterly data for the period 1983-88. The estimated models fit the data reasonably well and appear to be relatively stable. Money demand is found to be sensitive to changes in expected inflation. In the case of currency, demand increases in the short term in response to an increase in expected inflation even though there is a fall in demand in the long run. A 'cash-in-advance' explanation for this response pattern is suggested. It is also argued that the estimation results taken as a whole provide indirect evidence against the existence of substantial repressed inflation in China during the sample period. This is a working paper and the author would welcome any comments in the present text citatios should refer to and unpublished manuscript, mentioning the author and the date of issuance by the Internatinoal monetary Fund.